Correlation Between Testicular Biometrics and Serum Level of Reproductive Hormones of Crossed Arewa Breed of Stallions in Ilorin, Nigeria - Basiru, Afisu; Abdullahi, Ishola Olaide; Adakole, Adah Sylvanus; Jimoh, Akorede Ganiu; Abdulfatai, Aremu; Mistura, Azeez Oyebisi (Media Kedokteran Hewan, 2022)
The hypothalamic-pituitary-gonadal axis (HPG) controls the reproductive physiology activities of stallions. The organs involved in this axis are the hypothalamus, the pituitary, and the gonads (testes), and the endocrine secretions from these organs. This study determined the correlation between testicular measurements and reproductive hormones of cross Arewa stallion in Ilorin.  Forty-three crossed Arewa breeds of stallions were sampled. Testicular measurements (left and right testicular width, length, height, total testicular volume, and total testicular weight) were taken for each sample. Serum levels of sex hormones (Testosterone, luteinizing hormone, Follicle-stimulating, thyroid-stimulating hormone, and estradiol) were analyzed. The data obtained were presented as Mean±SD. Thereafter, the Pearson coefficient correlation between testicular biometrics and serum level of sex hormones was determined using SPSS® 16.0. The mean of the total testicular volume, the total testicular weight, and the gonadosomatic index were 400.80cm3, 1196.80cm3, and 301.20kg/cm3 respectively. There is a statistically significant correlation between testicular measurement and gonadosomatic index (p<0.05).These findings provide the testicular biometric data of cross Arewa stallion and can be used to determine the reproductive traits and or reproductive efficiency.